Outcomes of Treatment of Pectoralis Major Muscle Injury - Poliachenko, Yu.V.; Strafun, S.S.; Kulyk, Yu.A.; Lieskov, V.H. (TERRA ORTHOPAEDICA, 2023)
Background. The incidence of injuries to the pectoralis major muscle (PMM) is steadily increasing, necessitating an assessment of outcomes of surgical treatment. Objective: to analyze the outcomes of surgical treatment for PMM injuries. Material and Methods. The study is based on the analysis of surgical treatment outcomes of 84 patients with PMM injuries who were hospitalized in the Department of Microsurgery and Reconstructive Surgery of the Upper Extremity at the State Institution "Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine" from 2003 to 2023. The patients underwent a rehabilitation program and staged observation for up to 12 months after surgical intervention. The age of the patients ranged from 16 to 62 years; they were divided by age into three groups: up to 25 years, 25-40 years, and 41 years and older. Functional assessment of the PMM was performed using the Quick Disabilities of the Arm, Shoulder and Hand (Quick DASH), The Score and Subjective Evaluation by Patients with a Pectoral Major Tear (SEPPMT), and the American Shoulder and Elbow Surgeons (ASES) scales at the time of admission, at 6 months, and at 12 months after the surgery. Results. When comparing baseline functional parameters for acute and chronic PMM injuries using the Quick DASH, SEPPMT and ASES scales preoperatively, patients with acute injuries had worse results than those with chronic injuries (p < 0.001). At 6 months after surgical treatment, the group of patients with acute injuries showed significantly lower scores compared to the group with chronic injuries. At 12 months after surgical treatment, the group with acute injuries had significantly higher scores compared to the group with chronic injuries (p < 0.001), though still corresponding to excellent and good results. Conclusions. When comparing baseline functional parameters for acute and chronic PMM injuries using the Quick DASH, SEPPMT, and ASES scales preoperatively and at 6 and 12 months after surgical treatment, patients who underwent surgery within two weeks after the trauma demonstrated better results. In cases of chronic injuries, the results were slightly worse, but still were close to good results.